Implementation of Debtor Law in Force Majeure Credit Financing During The Covid-19 Pandemic - Wulandari, Mila Dianur; Mahmudah, Siti (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The COVID-19 pandemic has had an impact on the economy, especially the people of Kudus Regency. This research uses an empirical juridical approach, namely an approach that examines statutory regulations related to the issues to be discussed, and also takes a field approach to obtain information as supporting material. This research aims to analyze the implementation of the law and the legal consequences for debtors in Force Majeure in credit financing during the COVID-19 pandemic at PT. Bank Rakyat Indonesia Kudus Regency Unit Office. Implementation of law on debtors in Force Majeure credit financing during the COVID-19 pandemic at PT. BRI Kudus Regency Unit Office in accordance with POJK No.11 of 2020, the Bank can provide credit financing restructuring to debtors provided that the debtor is affected by the spread of COVID-19 which results in the debtor having difficulty fulfilling obligations to the Bank.